Preliminary Clinical Study on Therapy of Lidocaine Local Block Combined with Acupuncture-rehabilitation in Treatment of Post-stroke Upper Limb Spasticity - Ji LI; Li ZHANG; Ying GUAN; Lu WANG; Guile XIN; Yanli XING; Qiang TANG (康复学报)
Objective:To compare the clinical efficacy of Lidocaine local block combined with acupuncture-rehabilitation method and conventional acupuncture-rehabilitation method in the treatment of upper limb spasticity among post-stroke patients.Methods:Sixty cases of post-stroke upper limb spasticity patients who met the inclusion criteria in our hospital from June 2017 to June 2020, were selected. All the patients were randomly divided into observation group and control group, with 30 cases in each group. The control group was treated with conventional acupuncture-rehabilitation therapy, 6 times a week, for 4 weeks; the observation group was given Lidocaine local block therapy, 3 times a week, for 4 weeks. The Modified Ashworth Scale(MAS), Fugl-Meyer Assessment Upper Extremity(FMA-UE), Modified Barthel Index(MBI), and Active Range of Motion(AROM)scales were used to evaluate the changes of spasticity, motor function, activities of daily living, and elbow joint active range of motion.Results:There were no significant differences in MAS grade, FMA-UE, MBI, and AROM scores between the two groups before treatment(P>0.05), validating the comparisons between the two groups. The MAS grade, FMA-UE, MBI, and AROM scores of the two groups improved significantly after treatment compared with those before treatment, as the differences were statistically significant(P<0.01).In addition, MAS grade in the observation group exhibited a substantial improvement compared with the control group after treatment(P<0.01). The differences of FMA-UE scores before and after treatment in the observation and control groups were(14.7±3.7)and(9.7±2.5)points, respectively. The differences of MBI scores in the observation and control groups were(28.3±5.1)and(20.3±5.1)points, respectively. The differences of AROM scores in the observation and control groups were(42.0±34.5)and(25.5±18.7)points in the observation and control groups, respectively. Compared with the control group after treatment, the observation group showed substantial improvements in FMA-UE, MBI, and AROM scores, and the differences were statistically significant(P<0.05).Conclusion:Lidocaine local block combined with acupuncture-rehabilitation therapy shows good curative effect with post-stroke upper limb spasticity, as it could effectively reduce spasticity, enhance motor function and daily activity ability, and improve elbow joint activity ability.